أنموذج مقترح للتخطيط الإستراتيجي في الجامعات الأردنية في ضوء تقييم خططها الإستراتيجية - حوامدة، باسم علي عبيد (جامعة مؤتة, 2017)
This study aimed at developing a proposed model for strategic planning in Jordanian universities and assess the strategic plans of the universities of Jordan. To achieve the goal of the study, (21) strategy for universities Jordanian plan was analyzed, results of the study showed that the degree of availability of the elements of the strategic plan ranged ratios between (14% - 100%) and the majority of the elements came available with low-grade. It was the use of the curriculum developmental for the development of a model proposal for strategic planning for Jordanian universities. The proposed model consists of three basic stages: preparation stage include the formulation of the vision, mission and values, and analysis, formulation of objectives, and the stage of the application include: procedural plans, the stage of the evaluation and development which include: follow-up and evaluation, review and development. In light of the results of the study, a set of recommendations highlighted by the adoption of the proposed model, which was developed by the Jordanian universities.
هدفت هذه الدراسة إلى تطوير أنموذج للتخطيط الاستراتيجي في الجامعات الأردنية، ولتحقيق هدف الدراسة تم تحليل (21) خطة استراتيجية للوقوف على توفر عناصر الخطة الاستراتيجية فيها، وتراوحت نسب توفر هذه العناصر ما بين (14%-100%)، وغالبية العناصر جاءت متوفرة بدرجة منخفضة، وتم استخدام المنهج التطويري لتطوير أنموذج للتخطيط الاستراتيجي للجامعات الأردنية، وتكون الأنموذج المقترح من ثلاث مراحل أساسية؛ مرحلة الإعداد وتتضمن صياغة الرؤية والرسالة والقيم، والتحليل، وصياغة الأهداف، ومرحلة التنفيذ وتشمل الخطط الإجرائية، ومرحله التقييم والتطوير وتشمل المتابعة والتقييم والمراجعة والتطوير. وفي ضوء النتائج خرجت الدراسة بمجموعة من لتوصيات أبرزها تبني الأنموذج المطور من قبل الجامعات الأردنية.
Keywords: التعليم الجامعي -- التخطيط الإستراتيجي -- الجامعات الأردنية